Estimation of the neutron generation from gas puff Z-pinch on Qiang-Guang I facility - Liangping Wang (AIP Advances, 2019)
Z-pinch using a deuterium gas-puff load has been validated as a plasma neutron source on many accelerators such as Saturn, Z, Angara-5, and S-300. The experimental results on these accelerators show that the production of the neutron can be scaled as Yn∝Im4, where Yn is the yield and Im is the peak current of the accelerator, no matter what mechanism is eventually determined to be responsible for generating fusion neutrons. The neutron production on the Qiang-Guang I generator (1.5 MA, 100 ns) is analytically estimated that approximately 4 × 1010 D-D neutrons would be produced, among which the thermonuclear neutrons is only 7 × 107. The gas puff construction used on Qiang-Guang I is introduced, and the optimum line mass of the D2 gas is given. The results show that the optimum line mass is approximately 50 µg/cm for the driving current of Qiang-Guang I. The mass density distribution obtained with the classical ballistic-transport model demonstrates that the gas puff forms a hollow gas shell with the length of 2 cm. For D2 to produce a gas flow with the line mass of 50 µg/cm, the firing time of Qiang-Guang I changes to 250 µs and the absolute pressure of the chamber is increased to 4.2 atm.